Tensile strength of the posterior and anterior layer of the rectus abdominis muscle sheath in cadavers - Amorim,Carlos Roberto (2007)
PURPOSE: The aim of the present study was to assess, in cadavers, the resistance to medial traction of the posterior and anterior layer of the rectus abdominis muscle sheath. METHODS: An anatomical, prospective, self-controlled study was carried out in 20 male cadavers. An evaluation of the tension of the posterior and anterior layers of the rectus abdominis muscle sheath was performed following anatomical dissection of these structures. The traction necessary to advance the tissue ten millimeters was assessed using an analogic dynamometer. RESULTS: There was no significant statistical difference between the necessary traction at various levels of the anterior and posterior layers of the rectus sheath. However, medial advancement of the anterior layer of the rectus sheath required more traction strength than did advancement of the posterior layer to the midline. CONCLUSION: There is no difference in the tensile strength in the various levels of the anterior and posterior layers of the rectus sheath; however, medial advancement of the the anterior layer required more traction strength.